2021
DOI: 10.3390/plants10081738
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Evaluation of the Data Supporting Internal Use of Helichrysum italicum

Abstract: Helichrysum italicum is a Mediterranean plant with various pharmacological activities. Despite extensive reports on the bioactivity of the plant, its clinically studied applications have not yet been reviewed. The aim of our study was to gather information on the internal use of H. italicum and its bioactive constituents to determine its efficacy and safety for human use. We reviewed research articles that have not been previously presented in this context and analyzed relevant clinical studies with H. italicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…24 In a review of clinical trials, we found only six studies on the internal use of HI. 25 Even though it can be confirmed from those studies that the use of HI is safe, since no negative side effects were reported, not much can be concluded about the efficacy, as in most studies HI was used in combination with other herbs.…”
Section: Introductionmentioning
confidence: 97%
“…24 In a review of clinical trials, we found only six studies on the internal use of HI. 25 Even though it can be confirmed from those studies that the use of HI is safe, since no negative side effects were reported, not much can be concluded about the efficacy, as in most studies HI was used in combination with other herbs.…”
Section: Introductionmentioning
confidence: 97%
“…Its essential oil, hydrosol, as well as dried flowers and leaves, are also used in the preparation of beverages and in cooking [ 8 ]. Kramberger et al [ 9 ], evaluated the immortelle from the point of view of effectiveness and safety for internal use by reviewing the literature. They concluded that consumption of immortelle does not pose a health risk [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, rosmarinic acid is an ester of caffeic and 3,4-dihydroxyphenyllactic acid, while chlorogenic, neochlorogenic, isochlorogenic b and cichoric acids are esters of caffeic and quinic acid, thus belong to caffeoylquinic acid isomers, as following: 3-caffeoylquinic; 5-O-caffeoylquinic; 3,4-di-O-caffeoylquinic and 2,3-dicaffeoylquinic acid. The domination of caffeic acids esters (so-called quinic acid esters) in H. italicum raw materials was demonstrated earlier by other authors [17,20,[48][49][50].…”
Section: Content and Composition Of Phenolic Compoundsmentioning
confidence: 84%
“…The range of this diversity has already been summarized in review articles by Maksimovic et al [17], Ninčević et al [7] and Aćimović et al [10]. Among phenolic compounds, a lot of chemical subgroups have been identified in H. italicum, namely: flavonoids, acetophenones, phloroglucinols, tremetones, coumarins, phenolic acids, and their derivatives [17][18][19][20][21]. In relation to the presence of these secondary metabolites (both volatile and non-volatile), H. italicum extracts reveal a wide range of biological activities.…”
Section: Introductionmentioning
confidence: 95%